SISTEM TEKNOLOGI INFORMASI MANAJEMEN STRATEGI FUNGSIONAL RUMAH SAKIT MELALUI PENDEKATAN MODEL RANTAI NILAI - Rachman Suwandaru; Herlinah Herlinah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
To achieve competitive advantage, Hospitals need a strategy, which effectively requires the support of information systems. Implementation study on the role of information technology management strategy system in hospital management is intended to approach for customer / patient satisfaction, the achievement of organizational goals and enhance competitiveness (competitive adventage). The threat model and competition (competitive forces model) is used to explain the application of information technology in overcoming the competition externally. This study examines the approach model of the application of information technology systems with Value Chain Model (Value Chain Model). This model is used to know the application of Information Technology (IT) internally. Application of hospital information technology system with chain model using main activity and supporting activities. These activities are IT infrastructure, management, accounting, finance, HR management and so forth. Almost all hospitals have implemented Hospital Management Information System (SIMRS), so that the hospital business processes run in accordance with the vision and mission. Information Systems Model The hospital uses an integrated information system model on all poly management functions with reference to hospital development plans and using centralized management strategies for accurate decision-making.